Frequency of discrimination, harassment, and violence in lesbian, gay men, and bisexual in Italy. - Concetta P Pelullo (Public Library of Science (PLoS), 2013)
Background This cross-sectional study assessed the frequency of discrimination, harassment, and violence and the associated factors among a random sample of 1000 lesbian, gay men, and bisexual women and men recruited from randomly selected public venues in Italy. Methods A face-to-face interview sought information about: socio-demographics, frequency of discrimination, verbal harassment, and physical and sexual violence because of their sexual orientation, and their fear of suffering each types of victimization. Results In the whole sample, 28.3% and 11.9% self-reported at least one episode of victimization because of the sexual orientation in their lifetime and in the last year. Those unmarried, compared to the others, and with a college degree or higher, compared to less educated respondents, were more likely to have experienced an episode of victimization in their lifetime. Lesbians, compared to bisexual, had almost twice the odds of experiencing an episode of victimization. The most commonly reported experiences across the lifetime were verbal harassment, discrimination, and physical or sexual violence. Among those who had experienced one episode of victimization in their lifetime, 42.1% self-reported one episode in the last year. Perceived fear of suffering violence because of their sexual orientation, measured on a 10-point Likert scale with a higher score indicative of greater fear, ranges from 5.7 for verbal harassment to 6.4 for discrimination. Participants were more likely to have fear of suffering victimization because of their sexual orientation if they were female (compared to male), lesbian and gay men (compared to bisexual women and men), unmarried (compared to the others), and if they have already suffered an episode of victimization (compared to those who have not suffered an episode). Conclusions The study provides important insights into the violence experiences of lesbian, gay men, and bisexual women and men and the results may serve for improving policy initiatives to reduce such episodes.